2011
DOI: 10.1177/1077558710397761
|View full text |Cite
|
Sign up to set email alerts
|

General Practitioners and Clinical Practice Guidelines: A Reexamination

Abstract: General practitioners' (GPs') use of clinical practice guidelines (CPGs) may be influenced by various contextual and attitudinal factors. This study examines general attitudes toward CPGs to establish profiles according to these attitudes and to determine if these profiles are associated with awareness and with use of CPGs in daily practice. The authors conducted a cross-sectional telephone survey of 1,759 French GPs and measured (a) their general attitudes toward CPGs and (b) their awareness and use in daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…This proportion is similar to published findings from surveys carried out in general practice to assess knowledge about recommendations for six common diseases. However, the percentage of GPs stating that they applied recommendations (42%) was much higher in our study than reported for other diseases (17%) [35]. This led us to question the veracity of the GPs' statements, particularly because we were unable to detect any impact on the recognition of neuropathic pain and its therapeutic management.…”
Section: Discussioncontrasting
confidence: 83%
“…This proportion is similar to published findings from surveys carried out in general practice to assess knowledge about recommendations for six common diseases. However, the percentage of GPs stating that they applied recommendations (42%) was much higher in our study than reported for other diseases (17%) [35]. This led us to question the veracity of the GPs' statements, particularly because we were unable to detect any impact on the recognition of neuropathic pain and its therapeutic management.…”
Section: Discussioncontrasting
confidence: 83%
“…Our findings suggest that such doubts are a stronger factor in GPs' VH than is their perception of side effects. These doubts may also be linked to a tendency of some GPs to criticize official recommendations and guidelines, for example, because they consider them too constraining and ill adapted to the reality of practice and patients ( Clerc et al, 2011 ). GPs often identify the complexity of the vaccine schedule and its annual modifications for new vaccines and new guidelines as constraints ( Larson et al, 2011 , François et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the basis for lack of compliance to guidelines includes factors such as; concerns about loss of autonomy, guidelines being “too rigid”, oversimplification of the guidelines and their production being “motivated by a desire to cut costs” [36,37,44]. In addition, although a GP may have been in agreement with the guidelines, these are not necessarily congruent with patients’ wishes.…”
Section: Discussionmentioning
confidence: 99%